Current and Future Implications of COVID-19 among Youth Wheelchair Users: 24-Hour Activity Behavior - Ryan T. Conners; Lauren C. Bates; Patricia Pagan Lassalle; Gabriel Zieff; Paul N. Whitehead; Sandra Stevens; Lauren Killen; Robert Cochrum; Kathryn L. Rodebaugh; Mark Faghy; Lee Stoner (Children, 2021)
Preventative measures taken worldwide to decrease the transmission of COVID-19 have had a tremendous impact on youth. Following social restrictions, youth with and without physical disabilities are engaging in less physical activity, more increased sedentary behavior, and poor sleep habits. Specifically, youth wheelchair users (YWU) are likely disproportionately affected by COVID- 19 and have a higher risk of contraction due to underlying comorbidities. While we cannot control all of the negative long-term implications of COVID-19 for YWU, participation in positive 24-h activity behaviors can decrease chronic disease risk and the likelihood of long-term complications resulting from infection. This commentary is to extend the discourse on the importance of 24-h activity behaviors by focusing on YWU. Specifically, we discuss the importance of chronic disease prevention, provide a brief overview of 24-h activity behaviors, and outline some of the lessons that can be learned from the COVID-19 pandemic.